The Piast Poland by Paweł Jasienica from the Perspective of the Old and Contemporary Medieval Studies - Kowalska-Pietrzak, Anna (Sensus Historiae, 2019)
The Piast Poland by Pawel Jasienica was originally published in 1960 (English Edition in 1985) and has since been raising wide interest and popularity with readers. It has also become a subject of discussions both in academic and non-academic circles. Its explicit language and unusual narrative style made it outstanding, in comparison with other historical publications of that time. The author deliberately adopted an unconventional approach returning to traditional ways of presenting history. History academics recognized and prised his writing style, expertise and ways of transmitting information. Yet, he was also criticized for not complying with innovative approaches and ways the historical research of 1950s and 1960s were carried out and presented. For 60 years since it was published, the book has been generating an interest, especially among literary and historiography historians.